Simulation of a Flexible Mirror Performance in the Problem of Adaptive Compensation for Aberrations in an Optical System; Applied Mechanics and Materials; Vol. 756 : Mechanical Engineering, Automation and Control Systems (MEACS2014) - Kanev F. Yu. Fedor Yurievich (Modelling and Numerical Simulation, Algorithms and Mathematical Methods for Applied Problems, 2015)
Title screen